First description of male and immatures in mite genus Dasythyreus (Acari: Dasythyreidae) - Khaustov, Alexander A. (Zootaxa, 2020)
The male and immatural Dasythyreus polytrichus Khaustov and Abramov, 2010 (Acari: Dasythyreidae), collected from spruce bark in Western Siberia, Russia are described for the first time in the genus. Sexual dimorphism and leg setal development in this species are discussed.